Advantages of Teaching Based on International Programs in Primary Classes of Uzbekistan - Xurinisa Karimovna Qarshiboyeva (Web of Journals Publishing, 2023)
The study of advanced foreign experiences and the introduction of international standards are important in improving the quality and efficiency of education.
Keywords: international assessment programs, text, ideas, information, PIRLS, TIMSS, EGMA, EGRA.